2012
DOI: 10.5137/1019-5149.jtn.6176-12.0
|View full text |Cite
|
Sign up to set email alerts
|

Endonasal endoscopic skull base multilayer reconstruction surgery with nasal pedicled mucosal flap to manage high flow csf leakage

Abstract: AIm: Multilayer reconstruction of skull base using nasal pedicled mucosal flap has been widely accepted as a standard method for repairing high flow cerebrospinal fluid [CSF] leakage. In this study, we analyzed our outcome and summarized several valuable operation experiences from this technique. mAterIAl and methOds: This study included 20 consecutive patients who underwent endoscopic endonasal multilayer reconstruction using a nasal pedicled mucosal flap to repair high flow CSF leakage and were available fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…The general finding of these studies was that there is no significant difference in repair success rate between free tissue grafts and vascularized flaps, or for any other repair technique or material used. Results all fell within the standard overall success rate of 70% to 100% on first attempt,,,, and 86% to 100% on second attempt ,,…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…The general finding of these studies was that there is no significant difference in repair success rate between free tissue grafts and vascularized flaps, or for any other repair technique or material used. Results all fell within the standard overall success rate of 70% to 100% on first attempt,,,, and 86% to 100% on second attempt ,,…”
Section: Resultssupporting
confidence: 57%
“…There are a variety of different graft materials available for endoscopic repair of CSF leaks, including fat, bone, allografts, free mucosal grafts, and vascularized grafts, as well as glues or sealants to secure these materials in place. Following an extensive literature search on the topic of endoscopic repair for CSF rhinorrhea, the overall success rate ranges from 70% to 100% on first attempt,,,, and 86% to 100% on second attempt,, for all reported repair materials. We conducted a review of the available literature to determine if any of these methods are superior with supporting literature.…”
Section: Resultsmentioning
confidence: 99%
“…4 Xuejian reported a single death due to post-operative meningitis out of 20 patients investigated. 13 The latter study, however, did not specify the kind of mucosal vascular flap used in that particular patient. None of our patients had significant post-operative nasal synechiae, nasal obstruction or significant nasal crusting.…”
Section: Discussionmentioning
confidence: 99%
“…18 The autologous vascularized mucoperichondrial NSF is regarded as one of the most effective techniques for reconstruction of dural defects after endoscopic cranial base surgery. 1,13,[20][21][22][23][24] NSF usage has led to a decreased incidence of CSF leaks when compared with autologous avascular grafts and lumbar drain insertions, especially in high-flow CSF leak. 21,23 Zanation et al observed a postoperative CSF leak rate of 5.7% in a cohort of 70 patients who received an NSF for reconstruction after intradural lesion resection, but noted that other risk factors, such as age of patients, size of dural defect, and whether or not the patients received radiation therapy afterwards were correlated in the incidence of postoperative CSF leak.…”
Section: Discussionmentioning
confidence: 99%